Exploration of semiconducting properties of Zn(ii)- and Cd(ii)-based coordination polymers with dicarboxylate of a chair-type backbone. Issue 42 (15th October 2021) - Akhtaruzzaman,; Pal, Baishakhi; Khan, Samim; Dutta, Basudeb; Naaz, Sanobar; Maity, Suvendu; Ghosh, Prasanta; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : This study highlights the comparison of electrical properties and device applications of d 10 metal ion based coordination polymers. Abstract : A new Cd(ii )-based two-dimensional coordination polymer (2D CP) [{Cd2 ( cis -1, 4-chdc)2 (1, 10-phen)2 }·5H2 O] n (1 ) has been synthesized at room temperature by a slow diffusion technique using a 1, 4-cyclohexanedicarboxylic acid (1, 4-H2 chdc) and 1, 10-phenanthroline (1, 10-phen) mixed-ligand system. CP 1 was characterized by elemental analysis, infrared (IR) spectroscopy, powder X-ray diffraction (PXRD) analysis, single crystal X-ray diffraction (SCXRD) and thermogravimetric analysis (TGA) techniques. The structural analysis has revealed that CP 1 forms a 2D layer structure with guest water molecules encapsulated in the cavity generated by the Cd(ii ) centers and 1, 4-chdc anions. Interestingly, CP 1 shows electrical conductivity in the semiconductor region and behaves as a Schottky barrier diode. In order to compare the conductivity with a similar type of CP made of another d 10 metal ion Zn(ii ), a reported CP {Zn( cis -1, 4-chdc)(1, 10-phen)(H2 O)} n (2 ) with a 1D helical structure was synthesized and its conductivity was compared. CP 2 also exhibits electrical conductivity and reveals Schottky barrier diode behavior. However, it has been found that CP 1 shows better properties for electronic device application as compared to CP 2 .